The Impact of The COVID-19 Pandemic on The Shopping Tourism and Economy of A Border Region As Exemplified By The Poland-Belarus Borderland - Arkadiusz MALKOWSKI (Communications of International Proceedings, 2021)
This article presents selected findings of our research into shopping tourism and its impact on a region's economy. The research area focuses on the Poland-Belarus border. Both the theoretical and practical aspects of the role that shopping tourism plays in the development of peripheral areas are presented. The study makes use of quantitative secondary data,  primary information, and an analysis of the available source literature. The methods applied include a critical analysis of the source literature, a secondary data analysis, and in-depth interviews. The aim is to identify the problems caused by the COVID-19 pandemic and assess their impact on the development of the border area. The problems thus identified are: reduced border traffic, lower spending by foreigners in the borderland region, and cross-border trade regression. The analysis and evaluation show that the COVID-19 pandemic and the political dispute between Belarus and the European Union have affected the Poland-Belarus border area severely. The closed border is harmful to the region’s economy. The outcome of the study can be used in developing programs for counteracting the effects of the closed border.
Keywords: Cross-Border Area; Project Management; COVID-19; Pandemic; Polish-Belarusian Borderland.